Local control of T cell fate in lymph nodes safely and durably reverses myelin-driven autoimmunity - Senta M. Kapnick; Emily A. Gosselin; Shannon J. Tsai; Robert S. Oakes; Zahra A. Habibabady; Marian A. Ackun-Farmmer; Sean T. Carey; Shrey A. Shah; Ruochen Shen; Eugene Froimchuk; Haleigh B. Eppler; Christopher J. Bridgeman; et al. (Proceedings of the National Academy of Sciences, 2025)
Development of tolerogenic, antigen-specific immunotherapies could overcome limitations of existing treatments for inflammatory autoimmune diseases by achieving potent, durable remission without impacting healthy immune surveillance. Here, we deliver diffusion-limited polymer depots to lymph nodes to locally guide T cell fates for the treatment of multiple sclerosis (MS), an autoimmune disease that occurs when the immune system mistakenly attacks myelin. In preclinical MS models, depots loaded with myelin self-antigen and tolerizing cues mediate localized retention of activated CD4 T cells, promote myelin-specific regulatory T cells, and reshape inflammation in the central nervous system (CNS) to eliminate lesions. Selective disease reversal is achieved with a single treatment that induces long-lasting remission without hindering healthy responses to vaccine challenge with foreign antigen. Furthermore, depots offer favorable chemistry and manufacturing control features and are well tolerated in non-human primates. This work supports a clinically feasible concept for inducing safe, effective, antigen-specific tolerance without systemic or repeated dosing.